Value-added utilization of hydroxy-substituted aromatics in coal-derived liquids. (15th May 2023) - Ma, Zhi-Hao; Li, Sheng; Dong, Xue-Qian; Ju, Cai-Xia; Mu, Dan; Yang, Zheng; Li, Min; Guo, Xian-Hou; Zong, Zhi-Min; Cong, Xing-Shun; Wei, Xian-Yong
Graphical abstract: Hydroxy-substituted aromatics (HSAs) in coal-derived liquids (CDLs) are the raw materials of important value-added chemicals (VACs). CDLs and arenols in them were systematically analyzed. The method of separating arenols from CDLs is described in detail. Combined with the future research direction, the research direction of arenols in CDLs is proposed. Highlights: The types and formation mechanisms of coal-derived liquids (CDLs) are discussed. The content distribution and separation method of phenols in CDLs are elaborated. The idea for value-added utilization of phenols in CDLs is proposed. Abstract: Separating hydroxy-substituted aromatics (HSAs) from coal-derived liquids (CDLs) are of great attraction and significance for clean, low-carbon, safe, and efficient utilization of coal. In order to achieve the value-added utilization (VAU) of arenols, it is necessary to fully understand the types and processing methods of CDLs and arenols. This paper discusses in detail the types of CDLs and their arenols content, the formation mechanism, types, separation, and production methods of arenols. Subsequently, several strategies conducive to industrial development have been proposed for better VAU of HSAs in CDLs to increase the ongoing discussion on this topic.